Pendidikan Robbaniyyah dalam Perspektif Al-Qur'an - Surasman, Otong (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2020)
How important it is in modern times to return mankind back to the right path, after most humanshave taken many paths of life that are not true. As real proof is the loss of a good humanpersonality according to the nature of origin, where humans are born in a state of pure holiness.Then how important it is to explore rabbaniyyah education again, so that humanity can still beable to live life in this world in accordance with the nature of humanity. Now, to achieve allthis, there needs to be serious and disciplined efforts, so that by reestablishing the basicprinciples of life with rabbanuyah education will be realized, so as to create a life full ofharmony, peace, peace and fulfillment of all the needs of life, that is enough clothing , food andshelter, and free from poverty and ignorance and discrimination. To achieve that all of themneed clear and accurate solutions, then there is no other effort is to re-explore from the originalsource of Allah's guidance through the Holy Qur'an, which specifically explores rabbaniyyaheducation in the Qur'an. And more specific is to explore the verses of the Qur'an that are closelybound to humans as an-Nas (social beings), so that every human being will come to knowhimself as a human being.